Persistent Differences in Brain Structure in Developmental Dyscalculia: A Longitudinal Morphometry Study - McCaskey, Ursina; von Aster, Michael; O’Gorman, Ruth; Kucian, Karin (Frontiers in Human Neuroscience, 2020)
Developmental dyscalculia (DD) is a learning disability affecting the acquisition of numerical-arithmetical skills. Affected people show persistent deficits in number processing, which are associated with aberrant brain activation and structure. Reduced grey matter has been reported in DD for the parietal cortex including the intraparietal sulcus (IPS), but also for the frontal and occipito-temporal cortex. Furthermore, dyscalculics show white matter differences for instance in the inferior (ILF) and superior longitudinal fasciculus (SLF). However, the longitudinal development of these structural differences is unknown. Therefore, our goal was to investigate the developmental trajectory of grey and white matter in children with and without DD. In this longitudinal study, neuropsychological measures and T1-weighted structural images were collected twice with an interval of 4 years from 13 children with DD (8.2-10.4 years) and 10 typically developing (TD) children (8.0-10.4 years). Voxel-wise estimation of grey and white matter volumes was assessed by means of voxel-based morphometry for longitudinal data. The present findings reveal for the first time that DD children show persistently reduced grey and white matter volumes over development. Reduced grey matter was found in the bilateral inferior parietal lobes including the IPS, supramarginal gyri, left precuneus, cuneus, right superior occipital gyrus, bilateral inferior and middle temporal gyri, and insula. White matter volumes were reduced in the bilateral ILF and SLF, inferior fronto-occipital fasciculus, corticospinal tracts and right anterior thalamic radiation. Behaviorally, children with DD performed significantly worse in various numerical tasks at baseline and follow-up, corroborating persistent deficits in number processing. The present results are in line with the literature showing that children with DD have reduced grey and white matter volumes in the numerical network. Our study further sheds light on the trajectory of brain development, revealing that these known structural differences in the long association fibers and the adjacent regions of the temporal- and fronto-parietal cortex persist in dyscalculic children from childhood into adolescence. In conclusion, our results underscore that DD is a persistent learning disorder accompanied by deficits in number processing and reduced grey and white matter volumes in number related brain areas.